(untitled) (International Journal of Engineering and Computer Science, 2017)
We explore new ways in which Near Field Communication (NFC) can be used on smart phones. NFC allows for Contextual Application Invocation (CAI)—the execution of code on the phone as a result of our environment. We can launch applications because of contextual information we learn from another transaction on our phone, or we can associate with a context virtual token to recall at a later time. We can also pass context from one phone to another so the devices can interact in a multi-party session.